2006
DOI: 10.1007/s10637-006-9026-3
|View full text |Cite
|
Sign up to set email alerts
|

Transport of a novel anti-cancer agent, fenretinide across Caco-2 monolayers

Abstract: Fenretinide is a synthetic retinoid with chemotherapeutic activity against various malignancies. Upon oral administration to animals, fenretinide was found to be incompletely absorbed and excreted primarily in feces. The purpose of this study was to determine the possible reasons for poor oral absorption of fenretinide using Caco-2 cell monolayers. To achieve this purpose, a solid dispersion of fenretinide with Povidone K25 was used. The apparent permeability coefficient (P(app)) of fenretinide across Caco-2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
2
21
0
1
Order By: Relevance
“…The amount of drug within the cell membrane, ranging from 11.07% ± 1.34% for B2 to 16.91% ± 2.78% for B1, is in agreement with the findings of Kokate et al who found 13-15% of the initial amount of fenretinide within the cell membrane [32]. While some studies report minimal loss due to the cell monolayer [40], our studies revealed a significant proportion of the drug associated with the cell monolayer both within the cells and associated with the lipid membrane.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The amount of drug within the cell membrane, ranging from 11.07% ± 1.34% for B2 to 16.91% ± 2.78% for B1, is in agreement with the findings of Kokate et al who found 13-15% of the initial amount of fenretinide within the cell membrane [32]. While some studies report minimal loss due to the cell monolayer [40], our studies revealed a significant proportion of the drug associated with the cell monolayer both within the cells and associated with the lipid membrane.…”
Section: Resultssupporting
confidence: 91%
“…The supernatant was removed (representing the drug content in the cell cytosol), stabilized with ethanol (20% sample, 80% ethanol), and allowed to incubate overnight. The pellet remaining in the centrifuge tube (representing the drug content in the cell membrane) was also incubated with 1.5 mLethanol overnight [32]. The filter, now devoid of cells, was additionally incubated overnight with 2.0 mL of ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of these positive in vitro attributes, numerous oral cancer clinical trials have evaluated fenretinide (6,7). Complications such as low bioavailability and rapid drug elimination from the body (8,9), along with toxicity (e.g., mucositis and hyperlipidemia) (10,11), originating respectively after oral and intravenous administration, have impeded its use in chemoprevention for oral and other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The drug concentration for the cell permeation study was selected based on information obtained from the literature about fenretinide experimental concentrations in Caco-2 cell models [27]. BSA in the receiver compartment was used to improve sink conditions and reduce non-specific binding [28].…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was removed (representing the drug content in the cell cytosol), stabilized with ethanol (20% sample, 80% ethanol), and allowed to incubate overnight. The pellet remaining in the centrifuge tube (representing the drug content in the cell membrane) was also incubated with 1.5 mL of ethanol overnight [27]. Additionally, the Transwell® filter, now devoid of cells, was incubated overnight with 2.0 mL of ethanol.…”
Section: Methodsmentioning
confidence: 99%